Fluorescent tags to explore cell wall structure and dynamics - Gonneau, Martine; Höfte, Herman; Vernhettes, Samantha (Frontiers in Plant Science, 2012)
Plant cell walls are highly dynamic and heterogeneous structures, which vary between cell types, growth stages but also between microdomains within a single cell wall. In this review, we summarize the imaging techniques using fluorescent tags that are currently being used and which should in the coming years revolutionize our understanding of the dynamics of cell wall architecture and the cellular processes involved in the synthesis of cell wall components.